2020
DOI: 10.1111/acer.14502
|View full text |Cite
|
Sign up to set email alerts
|

Altered Resting‐State Neural Oscillations and Spectral Power in Children with Fetal Alcohol Spectrum Disorder

Abstract: Background Consumption of alcohol during pregnancy impacts fetal development and may lead to a variety of physical, cognitive, and behavioral abnormalities in childhood collectively known as fetal alcohol spectrum disorder (FASD). The FASD spectrum includes children with fetal alcohol syndrome (FAS), partial fetal alcohol syndrome (pFAS), and alcohol‐related neurodevelopmental disorder (ARND). Children with a FASD or prenatal alcohol exposure (PAE) have impaired white matter, reduced structural volumes, impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…The sample overlaps with the prior study ( Candelaria-Cook et al, 2020 ) which reported group differences in alpha power in children with FASD compared to TDC. Here we use the global and regional source spectral analysis reported in our prior work and add the analysis of specific DTI tracts to examine how MEG spectral power relates to white matter tract integrity assessed with DTI.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…The sample overlaps with the prior study ( Candelaria-Cook et al, 2020 ) which reported group differences in alpha power in children with FASD compared to TDC. Here we use the global and regional source spectral analysis reported in our prior work and add the analysis of specific DTI tracts to examine how MEG spectral power relates to white matter tract integrity assessed with DTI.…”
Section: Resultsmentioning
confidence: 86%
“…In our recently published results ( Candelaria-Cook et al, 2020 ), we identified a difference in alpha power in children with FAS relative to typically developing children (TDC). To assess the role of corticothalamic connectivity in generating alpha oscillations in children with an FASD relative to TDC, we extended the prior results ( Candelaria-Cook et al, 2020 ) using an overlapping sample to employ a multimodal approach using MEG to measure alpha normalized power at the sensor and source level and DTI to measure white matter integrity. Examining correlations at the sensor and source level allows us to determine the generalizability of the findings to the minimally processed sensor level data and is thus relevant to EEG studies that do not perform source analysis.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations